The morality of abortion and the deprivation of futures - Brown, M. (BMJ Group, 2000)
In an influential essay entitled Why abortion is wrong, Donald Marquis argues that killing actual persons is wrong because it unjustly deprives victims of their future; that the fetus has a future similar in morally relevant respects to the future lost by competent adult homicide victims, and that, as consequence, abortion is justifiable only in the same circumstances in which killing competent adult human beings is justifiable.(1) The metaphysical claim implicit in the first premise, that actual persons have a future of value, is ambiguous. The Future Like Ours argument (FLO) would be valid if "future of value" were used consistently to mean either "potential future of value" or "self-represented future of value", and FLO would be sound if one or the other interpretation supported both the moral claim and the metaphysical claim, but if, as I argue, any interpretation which makes the argument valid renders it unsound, then FLO must be rejected. Its apparent strength derives from equivocation on the concept of "a future of value". Key Words: Abortion • Future Like Ours • Donald Marquis • potentiality • pro-choice